Description of a Novel Fish Pathogen, Plesiomonas shigelloides subsp. oncorhynchi, Isolated from Rainbow Trout (Oncorhynchus mykiss): First Genome Analysis and Comparative Genomics - Muhammed Duman; Elena García Valdés; Hilal Ay; Soner Altun; Izzet Burcin Saticioglu (Fishes)
Plesiomonas shigelloides is the only species in its genus and has zoonotic importance due to the serious implications resulting from the consumption of contaminated seafood. This is the first report on the genomic features of the whole-genome sequence (WGS) of P. shigelloides strain V78, recovered from diseased rainbow trout, Oncorhynchus mykiss. The genome of P. shigelloides V78 consists of 4,478,098 base pairs (bps), which encode 3730 proteins, and has a G + C content of 51.1%. The bioinformatics analysis of WGS of V78 confirmed the presence of 121 tRNA genes and 42 rRNA genes (15 genes for 5S rRNA, 13 genes for 16S rRNA, and 14 genes for 23S rRNA). Comprehensive genome analyses revealed that the strain encodes secondary metabolites, antimicrobial resistance, and virulence genes. The strain V78 has 31 known antibiotic resistance models, which encode many antimicrobial resistances. In addition, strain V78 has 42 different virulence genes, such as adhesion, a secretion system, and motility. The digital DNA–DNA hybridization value against P. shigelloides NCTC 10360 was 74.2%, while the average nucleotide identity value was 97.1%. Based on the scrutinized analysis of genomic data, strain V78 should be considered a novel subspecies of P. shigelloides, for which Plesiomonas shigelloides subsp. oncorhynchi is proposed, with V78T as the type strain (=LMG 33380T=DSM 117059T).